ChemInform Abstract: Mesoscopic Features of Charge Generation in Organic Semiconductors. Issue 1 (January 2015) - Savoie, Brett M.; Jackson, Nicholas E.; Chen, Lin X.; Marks, Tobin J.; Ratner, Mark A.
Abstract Review: 38 refs.